The role of cognitive-behavioral psychotherapy in the treatment of Bipolar Disorder - Asanova, Azize (Psychosomatic Medicine and General Practice, 2021)
Background. Bipolar disorder (BD) is a chronic, recurrent condition that causes impaired quality of life and disability. This disorder is not only difficult for diagnosis, but also for maintenance and treatment. Apparently the most compliant patients get tired of constant medication. Therefore, it is important to understand how CBT can help patients overcome the shortcomings of pharmacotherapy and better control the various phases of the disease in both acute phase and remission. Results. There are enough techniques in the CBT to monitor symptoms in different phases of BD. Materials. Review of literature on the topic. Conclusions. CBT plays an important role in the maintenance and treatment of bipolar disorder. Living with BD is like running a "marathon" that will never end. If you look at the CBT / psychotherapist and their role in the life of a patient with BD - this is like "relationship" between coach and athlete. It is important to run this "marathon" and try not to go out of the race. This can be done only if you run consciously, calculating your strength, at the right pace to know how to breathe properly, how to find helpful thoughts so as not to fall or overestimate yourself and not make mistakes, how to change running technique, how to keep focus despite fatigue and exhaustion, how to achieve goals. CBT is a "Coach" who teaches how to run properly, technically, how fast, when to take a "break", when to accelerate, when to slow down during a "marathon". In addition, the coach supports, accepts, envy when the athlete is angry or crying from fatigue, wants to give up, but the marathon does not stop. The coach finds the right words, in a good Socratic way, to encourage the athlete not to stop running. And a life-long "marathon" can only be run by a well-trained athlete!